2021
DOI: 10.1111/aphw.12256
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distancing during the COVID‐19 pandemic: Letter writing with future self can mitigate negative affect

Abstract: Novel coronavirus disease (COVID‐19) is spreading across the world, threatening not only physical health but also psychological well‐being. We reasoned that a broadened temporal perspective may attenuate current mental distress and tested a letter‐writing manipulation designed to connect people to their post‐COVID‐19 future selves. We conducted an online experiment with 738 Japanese participants recruited from two common survey platforms. They were randomly assigned to either send a letter to their future self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The correlation magnitudes between the total score and affect were not substantially different among the affect dimensions ( r = .427 to .550 and −.474 to −.582 for the dimensions positively and negatively correlated with the total score, respectively). A previous study (Chishima et al, 2021) conducted a cluster analysis of the EACL. It demonstrated that the dimensions having positive correlations with the total score in this study (i.e., happiness, high-energy arousal, and low tense arousal) were aggregated as positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation magnitudes between the total score and affect were not substantially different among the affect dimensions ( r = .427 to .550 and −.474 to −.582 for the dimensions positively and negatively correlated with the total score, respectively). A previous study (Chishima et al, 2021) conducted a cluster analysis of the EACL. It demonstrated that the dimensions having positive correlations with the total score in this study (i.e., happiness, high-energy arousal, and low tense arousal) were aggregated as positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…One of the dimensions of psychological distancing includes temporal distancing, which causes consumer reactance that helps in mitigating the adverse effects of COVID-19 (Li et al, 2020 ). The study by Chishima et al ( 2021 ) explored temporal distancing in the COVID-19 context and explored consumer negative emotions that develop psychological reactance to restore freedom. The research of Li et al ( 2021 ) examined temporal distancing in the context of restaurants and explored its relationship with consumer evaluation, causing an unpleasant state of motivation.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, during COVID-19, we investigated customer psychological reactance because of psychological distance. A few studies referred to the relationship between psychological distancing and psychological reactance (Abel and Mcqueen, 2020 ; Reiss et al, 2020 ; Chishima et al, 2021 ; Finsterwalder, 2021 ; Zhang et al, 2021 ) and the psychological reactance to freedom restoration in the study of Moore and Fitzsimons ( 2014 ), Bessarabova et al ( 2017 ), and Zhang ( 2020 ). The work of Akhtar et al ( 2020 ) and Sakai et al ( 2021 ) also supported the relationship of psychological reactance with COVID-19 restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we compared writing to past-self versus writing to future-self. Research has shown that writing to one’s future-self can have a positive impact on mental health and well-being ( Chishima et al, 2021 ; Schippers et al, 2023 ). However, the mental process behind well-being achieved by writing to one’s future-self and that achieved by writing to one’s past-self might be different.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mental process behind well-being achieved by writing to one’s future-self and that achieved by writing to one’s past-self might be different. According to ( Chishima et al, 2021 ; Schippers et al, 2023 ), writing a letter to one’s future-self can clarify what one needs to work on to achieve one’s academic and career goals. In this sense, writing a letter to one’s future-self potentially creates anxious feelings by making oneself realize what is not sufficient for now, while writing a letter to one’s past-self comforts one’s feelings.…”
Section: Introductionmentioning
confidence: 99%